The activity testing of kesambi leaves (Scheichera oleosa) ethanol extract on white mice of the Balb/C strain induced by ovalbumin - Pacheco, Mergita Angela; Sunarni, Titik; Purwidyaningrum, Ika (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Asthma is a chronic inflammatory disorder of the respiratory tract that involves many cells. The anti-inflammatory effect of kesambi leaves is due to the presence of secondary metabolites. Flavonoid compounds are known to have potential effects as anti-inflammatory and antioxidants Method: This research uses the maceration method with 96% ethanol solvent. The test animals used were 26 white mice of the Balb/C strain which were divided into 6 treatment groups (N), (K-), (K+), (P1), (P2), (P3). Treatments on day 7 and day 14 were sensitized using OVA i.p. Next, on days 21, 23 and 25, 1% OVA was inhaled. On days 26 to 39, treatment was given, namely kesambi leaf extract (P1), (P2), (P3). On day 40, histopathologically discontinued. Data analysis using SPSS. Results: The yield of kesambi leaf extract was 28.2%. Data were analyzed using the Mann- Whitney and Wilcoxon tests at T0, T1 and T2 to determine differences in eosinophil counts. The results of the analysis of the eosinophil count were 70.23. Meanwhile, mast cell data analysis uses Mann Whitney 52.57 µm. Analysis of bronchiolar epithelial thickness data 73.33 µm. Conclusion: The effective dose of kesambi leaf ethanol extract is 400 mg/kgBW which can provide anti-asthma effects on blood eosinophils, mast cells and bronchiolar epithelial thickness in white mice induced by ovalbumin Balb/C.